The corticolous Physcietea lichen communities in the old parks of Kherson region (Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
The corticolous lichen communities in the old parks of Kherson region are presented by five new associations and two subassociations. Alyxorio varii-Xanthorietum parietinae has diagnostic species Alyxoria varia, Phaeophyscia nigricans, Scythioria phlogina and forms under influence of the sea winds in arid condition on a neutral bark of old trees (Fraxinus excelsior, F. pensilvanica, Populus alba, Salix alba). Melanelixio subargentiferi-Ramalinetum farinaceae has diagnostic species Melanelixia subargentifera, Phlyctis argena, Ramalina farinacea and colonize of the old trees with neutral bark (Fraxinus excelsior, Quercus robur) in shaded steppe forests and parks. Pioneer hemibasophilous, xerophilous, heliophylous association Rinodino pyrini-Calogayetum lobulatae forms on bark of the different trees in young parks of the southern Ukraine and differs from other nitrophylous communities by Calogaya lobulata, Myriolecis hagenii and Rinodina pyrina diagnostic species. These association are belong to the Xanthorion parietinae Оchsner 1928 alliance. Nitrophilous, heliophilous, xerophilous association Amandineo punctati-Xanthorietum parietinae subass. typicum is widespread in southern Ukraine on different tree species and has diagnostic species Amandinea punctata, Physcia adscendens and Xanthoria parietina. Subassociation Amandineo punctati-Xanthorietum parietinae subass. candelarielletosum efflorescentis has diagnostic species Pleurosticta acetabulum and Candelariella efflorescens and found in the old parks in southern Ukraine. Ombrophilous, scyophilous, mesophilous communities of the association Chaenotheco trichiali-Amandinietum punctatae has diagnostic species Amandinea punctata and Chaenotheca trichialis and forms on old trees at age 100–200 years (Quercus robur, Populus alba, P. nigra). It is member of alliance Buellion canescentis Barkman 1958. Lectotypes of association Buellietum punctiformis typicum Barkman 1958, Parmelietum acetabulae typicum Ochsner 1928, Physcietum adscendentis typicum Ochsner & Frey 1926 are selected.
Keywords: Physcietalia, Physcietum adscendentis, Xanthorietum parietinae, Parmelietum acetabulae, Buellietum punctiformis, Buellion canescentis, syntaxonomy.